Case Report: Heterozygous out-of-frame frameshift variant in ELANE without evidence of neutropenia - Li, Yulin; Yu, Lang; Zhang, Yishi; Zhang, Liwen; Zhou, Lina; Tang, Xuemei; Zhao, Xiaodong (Frontiers in Immunology, 2025)
Mutations in the ELANE gene, which encodes neutrophil elastase, are known to cause cyclic neutropenia (CyN) and severe congenital neutropenia (SCN). Currently, targeting ELANE for insertion-deletion to trigger nonsense-mediated mRNA decay (NMD) may be a simple and universal method to treat SCN caused by ELANE mutations. Here, we present a patient with a heterozygous out-of-frame frameshift variant (-2 frame indel) in exon 4 of the ELANE gene. The patient underwent whole exome sequencing during hospitalization for acute parotitis and bronchitis, and found a variant in ELANE, c.581_588del AGGCCGGC (p.Q194Rfs*93), inherited from the father. The father of the patient, without neutropenia, did not present any clinically significant symptoms and showed no evidence of somatic mosaicism. During the subsequent three-year follow-up period, the patient did not experience any other major infections, and neutrophil counts remained consistently within the normal range. More importantly, bone marrow cytology indicated mild granulocytic hypoplasia without evidence of maturation arrest. This case provides clinical evidence supporting the notion that late exon frameshift -2 frame indel insertions can inhibit mRNA translation efficiency and prevent the production of mutant proteins, thereby promoting neutrophil maturation. It also bolsters the ongoing development of gene therapy for ELANE-related diseases.